DISCOURSE ANALYSIS FOR ARCHITECTURE AND CONSTRUCTION STUDENTS: ADVANTAGES AND CHALLENGES IN IMPLEMENTING DISCOURSE ANALYSIS IN THE ESP CLASSROOM - Zakirova Khilola Abduraxmanovna; Dr. Yuslina Mohamad (Modern American Journals, 2025)
In the globalized and interdisciplinary landscape of architecture and construction, effective communication is as vital as technical proficiency. This paper explores the necessity of teaching discourse analysis (DA) to students in architecture and construction majors within an English for Specific Purposes (ESP) framework. Drawing on theoretical and empirical foundations, the article outlines the advantages of integrating DA into ESP courses, such as enhancing communicative competence, critical thinking, and genre awareness. It also addresses practical challenges, including curriculum design, student engagement, and disciplinary specificity. Real-life examples from architectural reports, project meetings, and academic presentations are analyzed to illustrate how DA can bridge linguistic knowledge with professional application.
Keywords: Discourse Analysis (DA); English for Specific Purposes (ESP); Architecture Education; Construction Communication; Genre Awareness; Communicative Competence; Curriculum Integration; Professional Language Use; Critical Thinking; Interdisciplinary Communication